Effect of nonlinear chirped Gaussian laser pulse on plasma wake field generation - Saeedeh Afhami; Esmaeil Eslami (AIP Advances, 2014)
An ultrashort laser pulse propagating in plasma can excite a nonlinear plasma wake field which can accelerate charged particles up to GeV energies within a compact space compared to the conventional accelerator devices. In this paper, the effect of different kinds of nonlinear chirped Gaussian laser pulse on wake field generation is investigated. The numerical analysis of our results depicts that the excitation of plasma wave with large and highly amplitude can be accomplished by nonlinear chirped pulses. The maximum amplitude of excited wake in nonlinear chirped pulse is approximately three times more than that of linear chirped pulse. In order to achieve high wake field generation, chirp parameters and functions should be set to optimal values.